Rational Choice and Moral Decision-Making in Research - Gordon, Anita M. (2014)
University psychology and sociology researchers rated the likelihood they would engage in misconduct as described in 9 research scenarios, while also making moral judgments and rating the likelihood of discovery and sanctions. Multiple regression revealed significant effects across various scenarios for moral judgment as well as shame and embarrassment on reducing misconduct. The effects on misconduct of the perceived probability of sanctions were conditioned on moral judgments in some scenarios. The results have implications for how universities address the prevention, detection, and sanctioning of research misconduct